Microbiological quality of water sources in the West region of Cameroon: quantitative detection of total coliforms using Micro Biological Survey method - Mabvouna Biguioh, Rodrigue (BMC Public Health, 2020)
BACKGROUND: Adequate supply of safe drinking-water remains a critical issue in most developing countries. The whole western region of Cameroon doesn’t have a sustainable continuous water supply system, which leads most people to use potentially contaminated water sources to meet their daily water needs. Previous, studies carried out in similar areas of Cameroon have highlighted the poor bacteriological quality of water sources used as drinking-water by the local populations. METHODS: This study used the Micro Biological Survey method, a rapid colorimetric test for the quantitative detection of Coliforms in water samples. 22 water sources (12 improved and 10 unimproved) were identified; 1 water sample of 50 ml was collected in sterile plastic tubes, immediately kept in a refrigerator box and transported to the laboratory for analysis. 1 ml of each sample was inoculated in the Coliforms Micro Biological Survey (Coli MBS) vials initially rehydrated with 10 ml of sterile distilled water. The Coli MBS vials were closed, shaken for about 30 s for homogenization and then incubated at 37 °C. From the initial red color of the Coli MBS vials, changes in color of the reaction vials were monitored at three different time intervals (12 h, 19 h and 24 h), corresponding to three levels of contamination. RESULTS: The average distance (8.7 m) of the latrines from the nearest water source was less than the minimal recommended distance (15 m) to ovoid external contamination. The pH of water samples ranged from 5.5 to 8.3 and the maximum temperature found (26 °C) was almost at level favorable to outbreaks of waterborne diseases such as cholera. The presence of Total Coliforms was detected in 90.91% of the samples. 40% of samples were positive 12 h after the analysis beginning. High level of contamination was observed in unimproved water sources, 50% after 12 h corresponding to Total Coliforms concentration of 10 < x < 103 CFU/ml and the other samples after 19 h (Total Coliforms concentration: 1 < x < 10 CFU/ml). CONCLUSION: This study revealed the poor microbiological quality of water used by local populations of our study sites. There is need to conduct further qualitative microbiology studies to isolate potential germs involved in outcome of diarrheal diseases.